Teaching attitudes among teachers at the Faculty of Medicine, University of Malaya - Jakiyah, D.; Jerilee, M.K.A.; Mazkiah, B.; Mohd, H.I.; El-Sabban, F. (Faculty of Medicine, University of Malaya, 1999)
This paper involves the obtained results of an 'Elective Program' project which was carried out by Phase I Medical Students of the 1998-1999 academic year at the Faculty of Medicine (POM), University of Malaya (UM). A questionnaire was designed to survey the attitudes of teachers at FOM-UM, the subject of choice of a 4 student group who were supervised by a faculty member. Students obtained a list of faculty members (teachers) of all academic departments from the Dean's Office and rehearsed their interviewing skills prior to collecting the data of the questionnaire, within a 1-week period. Respondents were 146 out of 275 in total (53%), which included all academic ranks and clinical and non-clinical teachers. Results showed that respondents were well qualified, have enough teaching experience and teach in a variety of forms. All teachers liked to teach and were motivated; however, 15% felt unhappy about their teaching and 6% did not think that their teaching was effective. The majority (96%) of teachers liked their teaching to be evaluated and many revealed several means to assist and motivate students. Teachers felt that there was room for improvement in the aspect of student-teacher interactions. Results of this project revealed that POM-UM is well endowed by qualified, motivated and caring teachers who wish for better interactions with their students.